Cytotoxicity of Philippine Carrageenan in COS-7 Cells - Briones, Annabelle V.; Sato, Toshinori (Asian Journal of Biological and Life Sciences, 2015)
This study is about the cytotoxicity of Philippine carrageenan (kappa, iota and lambda type) in COS-7 cells (African green monkey cell line producing T antigen of SV40). Results showed that among the carrageenan samples tested, lambda carrageenan has the highest cytotoxic activity as observed in the decrease of about 47.6 % cell viability when cells are incubated in longer time (48 h) with 0.0025% concentration. Shorter incubation period did not show any significant cytotoxic effect. Using a three-fold increase in concentration from 0.0025% to 0.0075%, lambda carrageenan gave the highest toxicity reading as compared to other types of carrageenan. Mild acid hydrolysis of carrageenan did not show high cytotoxic effect. Changes in cell morphology were observed at 48 hours incubation with lambda carrageenan.
Keywords: cell morphology; cell viability; Cellular toxicity; cytotoxicity; MTT assay